2017
DOI: 10.1245/s10434-017-5817-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Dexamethasone on the Magnitude of the Postoperative Systemic Inflammatory Response and Complications Following Surgery for Colorectal Cancer

Abstract: BackgroundThe magnitude of the postoperative systemic inflammatory response (SIR), as evidenced by C-reactive protein (CRP), is associated with both short- and long-term outcomes following surgery for colorectal cancer. The present study examined the impact of preoperative dexamethasone on the postoperative SIR and complications following elective surgery for colorectal cancer.MethodsPatients who underwent elective surgery, with curative intent, for colorectal cancer at a single center between 2008 and 2016 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…24 Furthermore, it has been observed that modulation of the postoperative systemic inflammatory response with perioperative corticosteroids is associated with fewer postoperative complications and improved survival; however, these findings are yet to be confirmed in prospective trials. 8,9 Allogeneic blood transfusion in the perioperative period is widely thought to be negatively associated with shortterm postoperative outcomes and survival in patients undergoing surgery for cancer, with an older Cochrane review, 4 a recent large propensity score matched study of over 4000 patients, 25 and a very recent comprehensive meta-analysis 3 reporting this to be the case. However, two propensity score matched cohorts from a single group of researchers found no negative impact on survival in colon 26 or rectal cancer, 27 and a smaller recent observational study found no independent impact of blood transfusion on colorectal cancer recurrence when corrected for preoperative anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, it has been observed that modulation of the postoperative systemic inflammatory response with perioperative corticosteroids is associated with fewer postoperative complications and improved survival; however, these findings are yet to be confirmed in prospective trials. 8,9 Allogeneic blood transfusion in the perioperative period is widely thought to be negatively associated with shortterm postoperative outcomes and survival in patients undergoing surgery for cancer, with an older Cochrane review, 4 a recent large propensity score matched study of over 4000 patients, 25 and a very recent comprehensive meta-analysis 3 reporting this to be the case. However, two propensity score matched cohorts from a single group of researchers found no negative impact on survival in colon 26 or rectal cancer, 27 and a smaller recent observational study found no independent impact of blood transfusion on colorectal cancer recurrence when corrected for preoperative anemia.…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of patients received postoperative nausea and vomiting prophylaxis in the form of intravenous dexamethasone during surgery, at the discretion of the consultant anesthetist. 8,12 During the study period, there was no formal perioperative blood transfusion protocol. As reported previously, 13 between June 2016 and June 2017 a preoperative iron replacement protocol was in place for the relatively small number of patients found to have true iron-deficient anemia.…”
Section: Patientsmentioning
confidence: 99%
“…Despite the widespread use of dexamethasone in the perioperative period of surgery, and numerous previously published studies, whether dexamethasone increases the risk of adverse reactions remains controversial. In this study, additional dexamethasone was given preoperatively, and no surgical site infection or gastrointestinal bleeding occurred during the observation period.…”
Section: Discussionmentioning
confidence: 89%
“…In recent 10 years, surgical techniques and perioperative management guidelines have made gratifying progress in THA, promoting the rapid recovery of patients. Tranexamic acid (TXA), a synthetic analog of lysine, inhibits fibrinolysis by competitively blocking the lysine binding site of plasminogen, often used for joint replacement to reduce perioperative blood loss, and it has anti‐inflammatory effects. Dexamethasone (DEX), with a strong anti‐inflammatory agent, has been widely used to reduce inflammatory markers, prevent PONV, and relieve postoperative pain and fatigue in various perioperative periods.…”
Section: Introductionmentioning
confidence: 99%
“…The increased survival outcomes one year after surgery in the glucocorticoid group were most likely not carried by a reduction in metastatic disease since no association was found for 1-year recurrence and since 1-year DFS was increased. Part of the improved 1-year survival might be contributed to by the previously described reduced postoperative complication rates associated with perioperative glucocorticoids [41].…”
Section: Discussionmentioning
confidence: 99%